THE REACTION OF THE INDONESIAN CAPITAL MARKET TO THE ANNOUNCEMENT OF THE 2024 PRESIDENTIAL ELECTION RESULTS OF THE REPUBLIC OF INDONESIA - Naufal Farhan Muhammad Sa’ad; Aisha Hanif (Antis Publisher, 2025)
Objective: This study aims to analyze the reaction of the Indonesian capital market to the announcement of the results of the 2024 Presidential Election of the Republic of Indonesia, which was officially announced on March 20, 2024. Method: The market reaction is examined using an event study approach with two main indicators: Abnormal Return and Trading Volume Activity on stocks listed in the LQ45 index on the Indonesia Stock Exchange. The data used are secondary data in the form of daily stock prices and trading volumes during a seven-day window before and after the announcement. The normality test results indicate that the data are normally distributed; thus, hypothesis testing was conducted using the Paired Sample t-test. Results: The analysis reveals no significant differences in the average Abnormal Return or Trading Volume Activity before and after the election announcement, with significance values of 0.922 and 0.591. Novelty: The study provides empirical evidence on the Indonesian capital market’s reaction to the official announcement of the 2024 Presidential Election results using a focused seven-day event window and two key indicators, Abnormal Return and Trading Volume Activity, and reveals that the market did not exhibit a significant reaction to the political event.